Feminization of Betta Fish (Betta splendens Regan) Through Embryo Immersion in Estradiol-17β Hormone Solution at the Dosages of 400 µg/I for 6, 12, 18 and 24 Hours - Purwati, S.; Carman, Odang; Junior, M. Zairin (Indonesian Society of Scientific Aquaculture (ISSA), 2004)
The experiment was carried out to study the effect of embryo immersion in estradiol-17β hormone solution on sex ratio, hatching rate and survival rate of betta fish. Eyed embryo were immersed in 400 µg/I estradiol-17β for 0 (control), 6, 12, 18 and 24 hours, and then the larva were reared until reaching three month old. Immersion in estradiol-17β hormone increased percentage in female, and the highest value was achieved at 12 hours of immersion. Increasing treatment duration to 24 hours decreased the survival rate of betta fish. The lowest value of hatching rate was found at 24 hours of immersion. Key words: Feminization, betta fish, betta splendens, sex ratio, survival rate and hatching rate